Use Of Mobile Device As An Assistive Technology For Learning Among Students With Special Needs - Ayodeji Obafemi; Ishola Ayodele Oluwaseun; Tolotunleke Adebayo (IJER (Indonesian Journal of Educational Research), 2021)
The aim of this study is to investigate the use of mobile device as an assistive technology for learning among students with special needs. Mobile technologies in the 21st century offer students’ opportunities to enhance the learning process. But the lack of the use of mobile devices continues to submerge the learning process and performance of students with special needs. Thus, the study focused on the use of mobile devices as an assistive technology for learning among students with special needs. The study is the descriptive research of the survey type. Population for the study comprised all students of colleges of education in Oyo state. The target population for the study were all hearing impaired students of college of education special, Oyo. Random sample technique was used to select 210 students. Two research questions and one hypothesis were raised for the study. A researcher designed questionnaire was used for the study. The study data were analysed using frequency, percentage, mean and t-test to answer research questions and test the hypothesis. Findings of the study revealed that students with special needs use mobile devices, and also had positive attitude towards the use of mobile devices as an assistive technology for learning. The study therefore recommended among others, that students with special needs should be exposed to other technologies and mobile device features that could further assist the learning process of the students.